Financial performance of JCS “ Russian railways” and its influence on possibility of attracting financial resources for financing of investment demands of railway transport - E. A. Shtele (Вестник СибАДИ, 2017)
The article swells upon the problem of reforming Russian railways. On the basis of studied material it is established that the actions, begun with reform, are insufficient for creating, in short terms, effective sources for renewal of basic funds. The large-scale attraction of financial resources in developing a sector hasn’t been happened, the conditions for steady growth and increasing competitiveness haven’t been created. The author suggests a method of applying financial analysis for the analysis of investment appeal of the company.